Antropogena effekter på sötvattenlevande tiofotade kräftdjur - Lidell, Viktoria (2021)
The world is facing many anthropogenic threats against biodiversity and ecosystems. For an ecosystem to work, all components in it, for example different species of animals and plants, temperature, and precipitation, are vital. Freshwater Decapods are an order of crustaceans referred to as key species in freshwater ecosystems. Freshwater ecosystems are particularly important for human and animal survival, and because of their limited extent they are endangered, mainly due to anthropogenic effects. The purpose of this literature study is to summarize and present research demonstrating the importance of Decapods for freshwater ecosystems, threats against them and potential solutions. Google Scholar and Primo have been the sources for the literature search. There are three main threats that have been detected by scientific research. Firstly, overfishing, which contributes to both population reduction and to the next major threat; pollution, ghost gear, which is directly harmful to animals and habitats and contributes to microplastics in both sea and freshwater; and thirdly, invasive species like the signal crayfish (Pacifastacus leniusculus), which has almost exterminated the Swedish native crayfish Astacus astacus. Potential solutions to these anthropogenic effects are many. One solution to the two first mentioned major threats is to reduce fishing which would serve against population decline as well as the amount of ghost gear that ends up in the water. Additionally, locating and removal of plastics and other debris from water is something that many organizations are devoted to, which is of great importance but may not be a solution to the underlying issue. Another measure is protected areas where fishing is restricted or prohibited, these areas have shown positive effects on both habitats and species population. By legislation, invasive species can be prevented and limited. Based on the research in this literature study it is found that a lot of information is known about anthropogenic threats towards freshwater ecosystems. However, further research and education is probably one of the main solutions for a long-term change, together with individual responsibility and restraint.